2015
DOI: 10.1259/bjr.20140406
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral limb vascular malformations: an update of appropriate imaging and treatment options of a challenging condition

Abstract: Peripheral vascular malformations encompass a wide spectrum of lesions that can present as an incidental finding or produce potentially life-or limb-threatening complications. They can have intra-articular and intraosseous extensions that will result in more diverse symptomology and present greater therapeutic challenges. Developments in classification, imaging and interventional techniques have helped to improve outcome. The onus is now placed on appropriate detailed preliminary imaging, diagnosis and classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 52 publications
1
85
0
2
Order By: Relevance
“…These 68 Ga-RGD PET/CT findings may have implications for treatment planning in patients with no clear nidus visible on angiography or patients with a complex or large AVM. Previous studies demonstrated that, for complex AVMs, the lack of standardized and accurate interpretation of images from conventional techniques hampers correct diagnosis and accurate treatment planning (25). Furthermore, 4D-CTA and plain angiography provide detailed information on the extent and angioarchitecture of the AVM, but further investigation is needed to evaluate if the angiogenic status of AVM can be used to determine which part of the AVM should be considered as therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…These 68 Ga-RGD PET/CT findings may have implications for treatment planning in patients with no clear nidus visible on angiography or patients with a complex or large AVM. Previous studies demonstrated that, for complex AVMs, the lack of standardized and accurate interpretation of images from conventional techniques hampers correct diagnosis and accurate treatment planning (25). Furthermore, 4D-CTA and plain angiography provide detailed information on the extent and angioarchitecture of the AVM, but further investigation is needed to evaluate if the angiogenic status of AVM can be used to determine which part of the AVM should be considered as therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular malformations more commonly represent isolated spontaneous lesions yet can be part of one of several syndromes such as Parkes Weber syndrome [1,3]. These typically grow commensurate with patient age, often in conjunction with hormonal changes, such as puberty and pregnancy [3][4][5][6]. Therefore, vascular malformations that are present at birth may not present clinically until adolescence or adulthood.…”
Section: Summary Of Literature Reviewmentioning
confidence: 99%
“…1,3,4 AVM is commonly present at birth in a quiescent stage. 3,4 The aberrant vascular growth is triggered by a variety of stimuli such as hormonal changes during puberty or pregnancy, thrombosis or infection.…”
mentioning
confidence: 99%
“…3,4 The aberrant vascular growth is triggered by a variety of stimuli such as hormonal changes during puberty or pregnancy, thrombosis or infection. [1][2][3] AVM can also emerge after trauma in adults. 2 Herein, we describe a case of AVM that manifested after subclavian central venous catheterization (CVC).…”
mentioning
confidence: 99%
See 1 more Smart Citation